PLD.39 Have intrapartum outcomes improved in the last decade?. (9th June 2014) - Harding, K; Seed, P; Marcelo, C
Abstract : Background: In the UK litigation rates in maternity care continue to rise despite increased consultant presence on delivery suite and mandatory CTG training. We decided to investigate the trend in low 5 min Apgar score (<7) as previous studies have shown a 3 fold risk in substandard care in babies with low Apgar at 5 min. 1 Objective: To asses if there are objective changes in intrapartum outcomes in the last decade. Methodology: Review of Apgar score from all singleton, term, labouring births (cephalic presentation) and total perinatal mortality rate and in a single tertiary unit between 2004 and 2013. Results: There were a total of 65, 651 births of which 568 babies had a low Apgar score. There has been a significant reduction in both low Apgar score RR 0.93 (CI 0.90–0.95) and total perinatal mortality RR 0.96 (CI.930 to 0.987), over the last decade (year on year change in rate). Conclusion: In this centre changes intrapartum care may have led to improved neonatal outcomes as demonstrated in reduced perinatal mortality and reduced numbers of babies born with low 5 min Apgar score (no change in emergency section rate). This may be a useful metric for assessing the quality of care.